Bounds of the Stardom: Media Image of Tomáš G. Masaryk as a Challenge for Theories of Film-star - Česálková, Lucie (Iluminace, 2009)
Meanings of the term film star not only in the narrower sense as a phrase about a particular personality, usually an actor, but also in the broader general sense of a professional non-actor personality with regard to his or her potential stardom. Analysis of hypothetical aspects of Tomáš Garrigue Masaryk's film stardom. Media image of Tomáš G. Masaryk, his construction through film, print, literature and photography. President Masaryk in documentary and reportage film, the so-called nonfictional representation. T. G. Masaryk about film.
Keywords: historical figures in film; presidents; documentary film; news film; Tomáš Garrigue Masaryk